The Development of Biodiversity Booklet in Mangunharjo Area - Zaida, Amalia; Rahayuningsih, Margareta (FMIPA UNNES, 2020)
Mangunharjo area is one of the areas in the coastal area of Semarang City that has biodiversity and can be used as an enviroment-based learning resource. The purpose of the study was to identified biodiversity and then analyzed the feasibility and readability of biodiversity booklet in the Mangunharjo area as a supplement of biological material. The research design was Research and Development (R&D). Small-scale trial was counducted at SMA Negeri 8 Semarang, class X MIPA 3 in the even semester of the 2019/2020 school year. The validation results showed that the booklet is very suitable for use in learning by getting a percentage of 98% media expert, 88% material expert, and 94% biology teacher. The results of small-scale trial with student response questionnaires obtained an average score of 88% in the excellent category, and readability booklet by students obtained a score of 94% in the high category.